Differences in Students' Emotion Regulation Based on Gender in SMA Negeri 1 Prabumulih - Diandra Rianatasya Arisa Noor; Nur Wisma; Alrefi Alrefi (Ma'soem University, 2024)
This research aims to determine differences in students' emotional regulation based on gender at SMA Negeri 1 Prabumulih. This research used a comparative descriptive method by conducting an independent sample t-test for hypothesis testing. The population used in this research was 213 class XI students using 68 students (34 females and 34 males) as samples. Data collection was carried out by distributing the Emotion Regulation Scale via Google Form. The mean value obtained from the data processing results was 119.35 for females and 116.47 for males. The highest value obtained in this research through measuring the emotional regulation scale was 135 and the lowest value was 98. Sig. (2-tailed) which was obtained at 0.057 with a significance level value of 0.1. Based on this value, it means that H0 is rejected and Ha is accepted. To determine whether the difference is significant or not, look at the t count and t table. Because the calculated t result’s 1.938 is greater than the t table’s 1.668, it can be concluded that there are significant differences in students' emotional regulation based on gender at SMA Negeri 1 Prabumulih.